2021
DOI: 10.1186/s12894-021-00824-5
|View full text |Cite
|
Sign up to set email alerts
|

Prostatic urethral lift (UroLift): a real-world analysis of outcomes using hospital episodes statistics

Abstract: Background To determine real-world outcomes of prostatic urethral lift (UroLift) procedures conducted in hospitals across England. Methods A retrospective observational cohort was identified from Hospital Episode Statistics data including men undergoing UroLift in hospitals in England between 2017 and 2020. Procedure uptake, patient demographics, inpatient complications, 30-day accident and emergency re-attendance rate, requirement for further trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…This is consistent with multiple ‘real world’ studies where procedural review of patient demographics reveals extreme ages including over 90 years. 10,11…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with multiple ‘real world’ studies where procedural review of patient demographics reveals extreme ages including over 90 years. 10,11…”
Section: Discussionmentioning
confidence: 99%
“…This is consistent with multiple 'real world' studies where procedural review of patient demographics reveals extreme ages including over 90 years. 10,11 The volume of bleeding associated complications could be related to urolift being performed in larger vascular prostates. While the European Association of Urology (EAU) guidelines recommend candidates for urolift being patients with prostate burdens <70 ml, urolift surgery in patients with burdens over 100 ml and even 200 ml have been reported in the literature.…”
Section: Key Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 5-year surgical retreatment rates were reported to be 4.4% with the most common transient mild adverse events including dysuria (16.9%), hematuria (11.8%), hematospermia (7.4%), urinary frequency and urgency of 13.6% at 5 years, that is, 2%-3% per year (Roehrborn et al, 2017). Page et al (2021) showed that in a real-world analysis of outcomes, Urolift had a higher retreatment rate of 11.9% at 2 years and hence surgeons had a lower threshold to offer Urolift itself as retreatment outside of clinical trials and patients had to undergo an alternate intervention for recurrent LUTS after Urolift. In our study cohort, 5 of the 19 patients had to seek a redo procedure within 2 years and had a median prostate volume of 64.0 ml.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the majority (> 95%) of complications in Urolift are minor in nature (Clavien grade 1) [26]. In a recent retrospective observational cohort study out of England, 99/2942 (3.4%) patients reported inpatient complications, with the most common adverse events being urinary retention (1.4%) followed by bleeding (0.9%) [27]. Furthermore, studies have demonstrated that sexual function appears to be preserved in PUL.…”
Section: Urolift (Prostatic Urethral Lift)mentioning
confidence: 99%